Exploring University Students’ Understanding of Intercultural Communication - Mia Rahmawati Yuwita (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Intercultural communication refers to the interaction between individuals from different lingua-cultural backgrounds. The study of intercultural communication has gained attention in the past decade as it provides an understanding of how multicultural people negotiate cultural differences in today’s globalized world. This study unpacks university students’ understanding of intercultural communication through online discussion forums. In particular, this article reviews their understanding and attitude towards diversity, specifically their views about ways of communication across cultures. This current research adopts a descriptive qualitative method, specifically classroom observation. There are approximately 60 students who joined the online discussion forums expressing their perspectives and ideas about what intercultural communication is. The result of this study evidently demonstrates students’ understanding and positive attitudes towards intercultural communication. They are aware that ways of communication might be distinctive and multicultural ways of thinking and doing could be benefited to engage in international-context communication in today’s globalized world. This study concludes the students’ sufficient intercultural communicative competence and their belief towards the benefits of intercultural communication dialogue. Thus, the impact of this research has affected not only students’ perceptions towards multeity but also the implications for overcoming those communication diversities